Dari doktrin ke makna: Rekonstruksi teologi Islam sebagai proyek Eksistensial - Transformatif dalam mengatasi kekosongan makna modern - Qurrotul Aini; Aura Durrotul; Zakia Salsabila; Ali Hasan Siswanto (Jurnal Pendidikan Agama Islam, 2026)
Contemporary Islamic theological studies are currently facing an academic crisis characterized by definitional stagnation, the loss of transformative urgency, and unproductive historical readings. The root of this problem lies in the dominance of doctrinal–normative approaches that tend to neglect the existential dimensions of modern human life, causing theology to lose its relevance in addressing issues of meaning, suffering, and alienation. The research gap emerges from the limited integration between Islamic theology and existential psychology, particularly in responding to the phenomenon of the existential vacuum. This study employs Viktor Frankl’s humanistic–existential framework, which emphasizes the concept of the will to meaning as the foundation of human meaningfulness. This research adopts a qualitative method with a philosophical-critical approach and hermeneutical analysis of classical and contemporary theological literature. The main argument of this article asserts that the crisis of Islamic theology is not merely a methodological crisis, but fundamentally an existential crisis resulting from the disconnection between doctrine and human experience. Therefore, a reconstruction of Islamic theology based on meaning-centered theology is required—one that is existential, interdisciplinary, and transformative in nature. The scholarly contribution of this study lies in the formulation of a new paradigm that integrates Islamic theology with existential logotherapy, thereby shifting the orientation of theology from merely producing truth-claims toward facilitating meaning-making. This approach is expected to revitalize the role of theology as a discipline that is not only normative, but also relevant in fostering existential awareness and humanistic consciousness.